2012
DOI: 10.1007/s10006-012-0331-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival and complications of zygomatic implants: a systematic review

Abstract: Despite the high survival rate observed, there is an impending need for conducting randomized controlled clinical trials to test the efficacy of these implants in comparison with the other techniques to treat the atrophic maxilla. Thus, the findings reported in the review must be interpreted with considerable caution. Moreover, more studies with longer follow-up periods involving adequate number of ZIs are needed. This will help to obtain a better understanding of the survival of ZIs in a long term. It is sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
122
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 42 publications
2
122
0
14
Order By: Relevance
“…(15) Recent systematic review, evaluated the level of survival and presence of complications in a period of 12 years. Only 42 studies or clinical cases of zygomatic implant were included in the criteria selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(15) Recent systematic review, evaluated the level of survival and presence of complications in a period of 12 years. Only 42 studies or clinical cases of zygomatic implant were included in the criteria selection.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the authors conclude the necessity of more studies with a long period of follow up. (15) In relation to the access, the opening of anterior wall, as practiced by the Caldwell Luc technique, contribute to more risk of complication postoperative as sensorial alterations, penetration of soft tissue inside of the sinus, creating sinusitis and other pathologies like surgical cysts. (17,18) However, authors showed the absence of the relation of the opening of anterior wall, in this surgery, with complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the posterior region, where bone quality and quantity are not always optimal, surgical alternatives have been proposed: short implants [10], onlay bone graft, sinus floor elevation, or implants in specific anatomical areas such as the zygomatic bone [11], the pterygoid region [12], or the maxillary tuber [13]. Each of these techniques have their own advantages and disadvantages, but they all have limitations and require advanced surgical expertise.…”
Section: Introductionmentioning
confidence: 99%